Vertebral augmentation by kyphoplasty and vertebroplasty: 8 years experience outcomes and complications - Yaltirik, Kaan (J Craniovertebr Junction Spine, 2016)
BACKGROUND AND CONTEXT: Minimally invasive percutaneous vertebral augmentation techniques; vertebroplasty, and kyphoplasty have been treatment choices for vertebral compression fractures (VCFs). The purpose of this study is to evaluate the outcomes of the patients who underwent vertebroplasty or kyphoplasty regarding complications, correction of vertebral body height, kyphosis angle and pain relief assessment using visual analog score (VAS) for pain. MATERIALS AND METHODS: A retrospective review of the hospital records for 100 consecutive patients treated with kyphoplasty or vertebroplasty in our department database. Patients with osteoporotic compression fractures, traumatic compressions, and osteolytic vertebral lesions, including metastases, hemangiomas, and multiple myeloma, were included in the study. Preoperative and postoperative VAS pain scores, percentages of vertebral compression and kyphotic angles were measured and compared as well as demographic characteristics and postoperative complications. Mobilization and length of stay (LOS) were recorded. RESULTS: One hundred patients were treated by 110 procedures. 64 patients were operated on due to osteoporosis (72 procedures). Twelve patients were operated on because of metastasis (13 procedures), 8 patients were operated on because of multiple myeloma (9 procedures). Five patients had two surgeries, 1 patient had 3 surgeries, and 1 patient had 5 surgeries. The mean preoperative VAS was 74.05 ± 9.8. In total, 175 levels were treated, 46 levels by kyphoplasty and 129 by vertebroplasty. The mean postoperative VAS was 20.94 ± 11.8. Most of the patients were mobilized in the same day they of surgery. Mean LOS was 1.83 days. Six patients had nonsymptomatic leakage of polymethlymethacrylate, and patient had epidural hematoma, which was operated on performing hemi-laminectomy. CONCLUSIONS: Percutaneous vertebroplasty and balloon kyphoplasty are both effective and safe minimally invasive procedures for the stabilization of VCFs. However, complications should be kept in mind during decision making.